A deep 96-well plate RBC storage platform for high-throughput screening of novel storage solutions - Nikulina, Maria; Nemkov, Travis; D'Alessandro, Angelo; Gaccione, Peter; Yoshida, Tatsuro (Frontiers in Physiology, 2022)
Background: Red blood cell (RBC) storage solutions, also known as additive solutions (ASs), first developed in the 1970s, enable extended storage of RBCs. Unfortunately, the advancements in this field have been limited, due to labor intensive and time-consuming serial in vitro and in vivo testing, coupled with very high commercialization hurdles. This study examines the utility of deep 96¬well plates for preliminary screenings of novel ASs through comparison of RBC storage with the standard PVC bags in terms of hemolysis and ATP levels, under both normoxic (N) and hypoxic/hypocapnic (H) storage conditions. The necessity for the presence of DEHP, normally provided by PVC bags, is also examined. Materials and methods: A pool of 2 ABO compatible RBC units was split between a bag and a plate. Each plate well contained either 1, 2 or 0 PVC strips cut from standard storage bags to supply DEHP. The H bags and plates were processed in an anaerobic glovebox and stored in O2 barrier bags. Hemolysis and ATP were measured bi-weekly using standard methods. Results: Final ATP and hemolysis values for the plate-stored RBCs were comparable to the typical values observed for 6-week storage of leukoreduced AS-3 RBCs in PVC bags under both N and H conditions. Hemolysis was below FDA and EU benchmarks of 1% and 0.8%, respectively, and excluding DEHP from plates during storage, resulted in an inconsequential increase when compared to bag samples. Discussion: In combination with high-throughput metabolomics workflow, this platform provides a highly efficient preliminary screening platform to accelerate the initial testing and consequent development of novel RBC ASs.